Brand Selection on Different Items - A study for Investigation of Bangladeshi Young Customer Priority Level - Prasad, Ripon Kumar; Jannat, Farhana; Ali, Ayub (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
Peoples mind, behavior and attitude are changed very quickly for the globalization & technology. Now a day’s Bangladeshi young customers are well informed about the clothing items and they spent more time for this. This paper explores Bangladeshi young customers buying behavior when they go to purchase different fashion items like- t-shirt, polo shirt, shirt and pant. Data is collected from 350 people from different area of Dhaka, Savar and Gazipur. Data is analyzed as first priority and second priority label for each fashion item. This research helps to know which brand product are got most priority for a particular item, which brand is doing well business in Bangladeshi fashion market etc. Many fashion maker or brand developer is helped by that to improve their fashion marketing, increasing customer demands and build a strong relationship with the customer.